The Effect of PUJB Subjects (Food Service Business Management) and Industrial Work Practice on Entrepreneurship Competence of Vocational School Students in Catering Service Expertise - Purwaningtyas, Kezia Eka; Nurlaela, Luthfiyah; Ismayati, Euis; Rijanto, Tri; Marniati, Marniati (International Journal for Educational and Vocational Studies, 2021)
This article aims to find out how food service business management subjects and industrial work practices affect the entrepreneurial competence of Vocational Education and Training (VET) students. The quantitative approach is to process the data and the numbers are obtained through statistical analysis. The data source used in this study is primary data or data obtained directly from respondents. This study aims to examine the effect of the independent variable (free), namely PUJB (X1), industrial work practice (X2) subjects on the dependent variable (dependent), namely entrepreneurial competence (Y). Researchers took a sample of 81 respondents. Data collection by giving questionnaires to respondents to all students majoring in marketing class XII at SMKN 2 Mojokerto. Based on the data from the results of research and tests that have been carried out, the conclusions are: (1) PUJB subjects affect the entrepreneurial competence of class XII students of the Catering Services study program at SMKN 2 Mojokerto. (2) Internship has an effect on the entrepreneurial competence of class XII students of the Catering Service study program at SMKN 2 Mojokerto. (3) PUJB and apprenticeship subjects affect the entrepreneurial competence of class XII students of the Catering Service study program at SMKN 2 Mojokerto.